2020
DOI: 10.1017/cem.2020.51
|View full text |Cite
|
Sign up to set email alerts
|

Regional anesthesia in Canadian emergency departments: Emergency physician practices, perspectives, and barriers to use

Abstract: Objectives Regional anesthesia has many applications in the emergency department (ED). It has been shown to reduce general anesthetic dose, requirement for post-procedural opioids, and recovery time. We sought to characterize the use of regional anesthesia by Canadian emergency physicians, including practices, perspectives and barriers to use in the ED. Methods A cross-sectional survey was administered to members of the Canadian Association of Emergency Physicians (CAEP), consisting of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…central neuraxial or peripheral nerve blocks). A Canadian study revealed that many emergency physicians expressed an interest in expanding their knowledge and improving the integration of regional anaesthesia techniques into their skillset [24]. However, less than half of them felt comfortable using (ultrasound-guided) regional anaesthesia techniques and indicated the need for additional training, on-the-job practice, protocols and support from the nursing staff.…”
Section: Use Of Regional Anaesthesia In the Department Of Emergency M...mentioning
confidence: 99%
“…central neuraxial or peripheral nerve blocks). A Canadian study revealed that many emergency physicians expressed an interest in expanding their knowledge and improving the integration of regional anaesthesia techniques into their skillset [24]. However, less than half of them felt comfortable using (ultrasound-guided) regional anaesthesia techniques and indicated the need for additional training, on-the-job practice, protocols and support from the nursing staff.…”
Section: Use Of Regional Anaesthesia In the Department Of Emergency M...mentioning
confidence: 99%
“…However, there are important barriers to emergency physician training in UGRA. First, the ED is a time-pressured environment in which it can be challenging to learn new procedural skills 3 .…”
mentioning
confidence: 99%